2021
DOI: 10.1111/den.13982
|View full text |Cite
|
Sign up to set email alerts
|

The role of advanced endoscopy in the management of inflammatory digestive diseases (upper gastrointestinal tract)

Abstract: The Japan Gastroenterological Endoscopy Society held four serial symposia between 2019 and 2020 on the state-of-the-art of issues related to upper GI inflammatory diseases. This review discusses some of the topics addressed in these symposia. The papers regarding nonerosive reflux disease, recent improvements in intraesophageal pH-impedance monitoring and endoscopic diagnosis using image-enhanced endoscopy have been published. Many publications have addressed its usefulness in endoscopic treatment of gastroeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…In the Kyoto Classification of Gastritis, atrophy, intestinal metaplasia, diffuse redness, and nodularity are risk factors for gastric cancer [ 22 , 24 , 25 , 26 , 27 , 28 ]. Enlarged fold has also been weakly associated with undifferentiated gastric carcinoma [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Kyoto Classification of Gastritis, atrophy, intestinal metaplasia, diffuse redness, and nodularity are risk factors for gastric cancer [ 22 , 24 , 25 , 26 , 27 , 28 ]. Enlarged fold has also been weakly associated with undifferentiated gastric carcinoma [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Kyoto Classification of Gastritis allows efficient evaluation of gastric cancer risk based on the state of the background mucosa with 19 endoscopic findings. In particular, diffuse redness, mucosal swelling, enlarged fold, sticky mucus, and spotty redness are considered findings suggestive of H. pylori infection [ 14 , 15 , 16 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, endoscopic ultrasonography (EUS) and high‐resolution manometry (HRM) may be used for diagnosis or evaluations of treatment outcomes. In a recent study using EUS and HRM, the significantly thicker muscle layer and higher distal contractile integral (DCI) values were recognized in the symptomatic group than the asymptomatic group, and esophageal wall thickness and DCI values as well as EoE symptoms were significantly improved after treatment 1 . Further studies are required to confirm the usefulness of those modalities for EoE predictors.…”
Section: Eosinophilic Esophagitismentioning
confidence: 99%
“…In contrast, it has been reported that lugol chromoendoscopy and image enhanced endoscopy such as auto fluorescence imaging, narrow band imaging, and linked color imaging compared with WLI may improve visibility and reliability for non‐erosive reflux disease (NERD) diagnosis. On the other hand, 24‐h intra‐esophageal pH‐impedance monitoring can be used to confirm NERD and differentiate it from functional heartburn 1 …”
Section: Reflux Esophagitismentioning
confidence: 99%